Optimizing Palm Oil Plantation Productivity Using Offline Blockchain and Drone Rover Solutions - Aryanto, Aryanto; Cipta, I Nengah Marccel Janara Brata; Putri, Dinda Armeylia; Amelia, Bella; Pratama, Muhammad Herly (Jurnal Rekayasa Elektrika, 2024)
The increasing demand for sustainable palm oil production challenges plantations to maintain efficient management and data transparency, particularly in remote areas with limited internet access. This study aims to develop and implement an offline blockchain system integrated with drone rover devices to support data collection and decision-making without internet connectivity. Drone rovers equipped with sensors and cameras are deployed to collect comprehensive data on plant health, pest detection, and environmental conditions across the plantation. The offline blockchain securely stores this data, ensuring integrity and traceability. Additionally, an AI system is utilized to process this data in real-time, enhancing the precision of monitoring plant health and fruit ripeness. Results indicate that this approach optimizes resource management, improves operational transparency, and enables accurate decision-making in palm oil plantation management. By combining offline blockchain technology with AI-driven analysis, this study provides a scalable and effective solution for sustainable agriculture in connectivity-challenged environments.